Interaction potential between two spheres mediated by excluded volume polymers. - Tuinier, R; Lekkerkerker, H; Aarts, D (2002)
The interaction between two spheres in a solution of nonadsorbing polymers, with excluded volume interaction, is calculated from the depletion layers around the spheres using the generalized Gibbs adsorption equation. By combining the bulk correlation length with the curvature-dependent interfacial tension between a sphere and the surrounding polymer solution [Hanke, Eisenriegler, and Dietrich, Phys. Rev. E 59, 6853 (1999)], the depletion layer thickness around a sphere is obtained. The resulting contact potential agrees with a scaling prediction of de Gennes in the semidilute regime.